Comparison of high fibre diets, basal insulin supplements, and flexible insulin treatment for non-insulin dependent (type II) diabetics poorly controlled with sulphonylureas. Issue 6650 (17th September 1988) - Scott, A. R.; Attenborough, Y.; Peacock, I.; Fletcher, E.; Jeffcoate, W. J.; Tattersall, R. B.
Abstract : OBJECTIVE--To compare high fibre diet, basal insulin supplements and a regimen of insulin four times daily in non-insulin dependent (type II) diabetic patients who were poorly controlled with sulphonylureas. DESIGN--Run in period lasting 2-3 months during which self monitoring of glucose concentration was taught, followed by six months on a high fibre diet, followed by six months' treatment with insulin in those patients who did not respond to the high fibre diet. SETTING--Teaching hospital diabetic clinics. PATIENTS--33 patients who had had diabetes for at least two years and had haemoglobin A1 concentrations over 10% despite receiving nearly maximum doses of oral hypoglycaemic agents. No absolute indications for treatment with insulin. INTERVENTIONS--During the high fibre diet daily fibre intake was increased by a mean of 16 g (95% confidence interval 12 to 20 g.) Twenty five patients were then started on once daily insulin. After three months 14 patients were started on four injections of insulin daily. ENDPOINT--Control of diabetes (haemoglobin A1 concentration less than or equal to 10% and fasting plasma glucose concentration less than or equal to 6 mmol/l) or completion of six months on insulin treatment. MEASUREMENTS AND MAIN RESULTS-- No change in weight, diet, or concentrations of fasting glucose or haemoglobin A1 occurred during run in period. During high fibre diet there were no changes in haemoglobin A1 concentrations, but mean fasting glucose concentrations rose by 1.7 mmol/l (95% confidence interval 0.9 to 2.5, p less than 0.01). With once daily insulin mean concentrations of fasting plasma glucose fell from 12.6 to 7.6 mmol/l (p less than 0.001) and haemoglobin A1 from 14.6% to 11.2% (p less than 0.001). With insulin four times daily concentrations of haemoglobin A1 fell from 11.5% to 9.6% (p less than 0.02). Lipid concentrations were unchanged by high fibre diet. In patients receiving insulin the mean cholesterol concentrations fell from 7.1 to 6.4 mmol/l (p less than 0.0001), high density lipoprotein concentrations rose from 1.1 to 1.29 mmol/l (p less than 0.01), and triglyceride concentrations fell from 2.67 to 1.86 mmol/l (p less than 0.05). Patients taking insulin gained weight and those taking it four times daily gained an average of 4.2 kg. CONCLUSIONS--High fibre diets worsen control of diabetes in patients who are poorly controlled with oral hypoglycaemic agents. Maximum improvements in control of diabetes were achieved by taking insulin four times daily.